Fetal Alcohol Spectrum Disorder Standards: Supporting Children in the Care of Children’s Services - Badry, Dorothy (First Peoples Child & Family Review)

(untitled) (First Nations Child and Family Caring Society of Canada, 2009)
The purpose of this research was to examine the utilization of enhanced practice standards for children in care with Fetal Alcohol Spectrum Disorder (FASD). Children in care with FASD represent a vulnerable population and require multiple supports from a cross-disciplinary perspective. Children removed from the care of their parents were identiﬁed as having needs beyond standard care provided within Children’s Services in Alberta. To address this concern a project was initiated in 2002 and completed in 2005 which identiﬁed positive beneﬁt from an increase in caseload hours for workers responsible for children with FASD in the Aboriginal Unit including more contact with children and additional supports for foster parents. Standards regarding family visitation are also highlighted. An additional casework position was developed in order to decrease caseloads and meet the standards. Changing the way child welfare and foster care services are delivered for children with FASD is an important phenomenon to study and this research may guide future interventions.